Do Cross-National and Ethnic Group Bullying Comparisons Represent Reality? Testing Instruments for Structural Equivalence and Structural Isomorphism - Samara, Muthanna; Foody, Mairéad; Göbel, Kristin; Altawil, Mohamed; Scheithauer, Herbert (Frontiers in Psychology, 2019)
Bullying in schools is a widespread phenomenon, witnessed worldwide, with negative consequences for victims and perpetrators. Although it is an international issue, there are several issues with cross-national and cross-cultural/ethnic research that can make comparisons between countries and cultures/ethnic groups difficult including language, cultural perception, and/or methodological issues. As statistical techniques rapidly develop, there may be more scope to be statistically creative in how we assess the utility of one tool across different groups such as cultures, nations, etc. At the very least, an attempt to do this should be paramount in studies investigating different groups (e.g., from different countries) at one time. This study investigated bullying and victimization rates in a large cross-ethnic and -country comparison between adolescents from four countries and five different ethnic groups including: Israel (Jewish Israelis and Arab Palestinian Israelis), Palestine (the Gaza Strip), Germany, and Greece. A total of 3,186 school children aged 12–15 years completed self-report questionnaires of peer bullying/victimization. A stepwise data analytic approach was used to test comparability of the psychometric properties: (1) Structural equivalence contributes to the valid use of the instrument in cultural contexts other than the one for which the instrument has been developed. Structural equivalence is a necessary condition for the justification of indirect or direct comparisons between cultural groups. (2) Additionally, structural isomorphism is necessary to demonstrate that the same internal structure of the instrument applies to the cultural and individual levels. Findings support the internal structural equivalence of the questionnaire with the exception of the Palestinian sample from the Gaza Strip. Subsequently, exploratory factor analysis on the cultural level structure revealed a one-factor structure with congruence measure below 0.85. Thus, no evidence was found for internal structural isomorphism suggesting that no direct comparisons of cultural samples was justified. These results are discussed in detail and the implications for the international research community and cross-national/-ethnic comparison studies in bullying are addressed.